2022
DOI: 10.1101/2022.12.26.22283900
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multisite Study of Optical Genome Mapping of Retrospective and Prospective Constitutional Disorder Cohorts

Abstract: Several medical societies including the American College of Medical Genetics and Genomics, the American Academy of Neurology, and the Association of Molecular Pathology recommend chromosomal microarray (CMA) as the first-tier test in the genetic work-up for individuals with neurodevelopmental disorders such as developmental delay and intellectual disability, autism spectrum disorder, as well as other disorders suspected to be of genetic etiology. Although CMA has significantly increased the diagnostic yield fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In addition, Newman et al reported that 17% of duplications are not tandem, but rather complex rearrangements such as insertional translocations, which may result in fusion or disrupted genes with clinical phenotypes 24 . Recently, Broeckel et al reported that OGM identified a 69‐kbp duplication from chromosome 4 inserted in the X‐chromosome, leading to potential fusion with BCLAF3 on the X‐chromosome 25 . Stevenson et al reported that OGM revealed a 43.1 Mb gain of 2q31.2q36.1 inserted interstitially in an inverted orientation into 14q32.33, disrupting the JAG2 gene 21 (OMIM*602570).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Newman et al reported that 17% of duplications are not tandem, but rather complex rearrangements such as insertional translocations, which may result in fusion or disrupted genes with clinical phenotypes 24 . Recently, Broeckel et al reported that OGM identified a 69‐kbp duplication from chromosome 4 inserted in the X‐chromosome, leading to potential fusion with BCLAF3 on the X‐chromosome 25 . Stevenson et al reported that OGM revealed a 43.1 Mb gain of 2q31.2q36.1 inserted interstitially in an inverted orientation into 14q32.33, disrupting the JAG2 gene 21 (OMIM*602570).…”
Section: Discussionmentioning
confidence: 99%
“…24 Recently, Broeckel et al reported that OGM identified a 69kbp duplication from chromosome 4 inserted in the X-chromosome, leading to potential fusion with BCLAF3 on the X-chromosome. 25 Stevenson et al reported that OGM revealed a 43.1 Mb gain of 2q31.2q36.1 inserted interstitially in an inverted orientation into 14q32.33, disrupting the JAG2 gene 21 (OMIM*602570). Although these insertional duplications found by OGM are reported as variants of unknown significance, we believe that the ability of OGM to localize the additional duplicated fragments would be beneficial for exploring pathogenic duplications omitted by SOC testing.…”
Section: Complex Casesmentioning
confidence: 99%
“…Therefore, versions of Basic Protocol 1 (with slight variations depending on the cell types covered) have also been published in previous Current Protocols manuscripts that describe methods using Bionano OGM (Koppikar et al, 2023;Sahajpal et al, 2023). In addition, future Current Protocols manuscripts describing the Bionano OGM method will contain the same Basic Protocol 1 (Broeckel, 2024;Kanagal-Shamanna, 2024).…”
Section: Genomic Ultra-high-molecular-weight Dna Isolation Labeling A...mentioning
confidence: 99%